Distributed fault diagnosis for networked nonlinear uncertain systems - Shahnazari, Hadi; Mhaskar, Prashant (Computers & chemical engineering, 2018)
•A distributed framework for simultaneous actuator and sensor fault diagnosis in nonlinear uncertain networked systems.•Designing time-varying thresholds that enable retaining detectability and isolability properties of local FDI schemes in the presence of fault in the shared interconnections of the network.•Introducing notion of detectability index that measures the probability of a sensitive residual breaching its threshold.•Effectiveness of the proposed methodology is shown via application to a reactor-separator process subject to uncertainty and measurement. In this work, we address the problem of simultaneous fault diagnosis in nonlinear uncertain networked systems utilizing a distributed fault detection and isolation (FDI) strategy. The key idea is to design a bank of local FDI (LFDI) schemes that communicate with each other for improved FDI. The proposed distributed FDI scheme is shown to be able to handle local faults as well as those that affect more than one subsystem. This is achieved via appropriate adaptation of the LFDI filters based on information exchange with other subsystems and using the proposed notion of detectability index. The detectability index and isolability conditions are rigorously derived for the distributed FDI scheme. Effectiveness of the proposed methodology is shown via application to a reactor-separator process subject to uncertainty and measurement noise.